Early predictors of objectively measured physical activity and sedentary behaviour in 8-10 year old children: the Gateshead Millennium Study. - Mark S Pearce; Laura Basterfield; Kay D Mann; Kathryn N Parkinson; Ashley J Adamson; John J Reilly; Gateshead Millennium Study Core Team (PLoS ONE)
Background With a number of studies suggesting associations between early life influences and later chronic disease risk, it is suggested that associations between early growth and later physical activity (PA) may be a mediator. However, conflicting evidence exists for association between birth weight and childhood PA. In addition, it is important to know what other, potentially modifiable, factors may influence PA in children given its' association with childhood and later adiposity. We used the Gateshead Millennium Study (GMS) to identify predictors of childhood PA levels. Methods The GMS is a cohort of 1029 infants born in 1999-2000 in Gateshead in northern England. Throughout infancy and early childhood, detailed information was collected. Assessments at age 9 years included body composition, objective measures of habitual PA and a range of lifestyle factors. Mean total volumes of PA (accelerometer count per minute, cpm) and moderate-vigorous intensity PA (MVPA), and the percentage of time spent in sedentary behaviour (%SB) were quantified and related to potential predictors using linear regression and path analysis. Results Children aged 8-10 years were included. Significant differences were seen in all three outcome variables between sexes and season of measurement (p<0.001). Restricting children's access to television was associated with decreased MVPA. Increased paternal age was associated with significant increases in %SB (p = 0.02), but not MVPA or total PA. Increased time spent in out of school sports clubs was significantly associated with decreased %SB (p = 0.02). No significant associations were seen with birth weight. Conclusion A range of factors, directly or indirectly, influenced PA and sedentary behaviour. However, associations differed between the different constructs of PA and %SB. Exploring further the sex differences in PA would appear to be useful, as would encouraging children to join out of school sports clubs.